Towards a sustainable campus: zero single-use plastic campaign - Azmi, Azlin Suhaida; Fatah Yasin, Raudlotul Firdaus; Zainan Nazri, Nurul Jannah (IIUM Press, International Islamic University Malaysia, 2020)
Plastics are man made polymeric organic materials, which can be moulded into many shapes for various uses. They are lightweight, durable and long-lasting and usable for multiple purposes. Plastic find their use in practically every industrialised consumer item, especially in packaging and shopping bags, However, irresponsible and disproportionate use of plastics has created a waste mis-management crisis at a global scale. This chapter discusses plastic waste and the Zero Single-use plastic Campaign at the International Islamic University Malaysia (IIUM). The campaign is designed to create awareness on the harms of single-use plastic items, and to discourage single-use plastics among the IIUM community. The chapter examines the project's efficacy in educating society, specifically the IIUM community ad how such campaigns can protect the environment from further damage and destruction caused by plastic waste.